THE ROLE OF FINTECH IN INCREASING ACCESS TO ECONOMIC GROWTH FOR MARGINALIZED COMMUNITIES - Sania; Diana Octavia H; Qurrota A'yun (Al-Qalam Institute, Probolinggo, East Java, Indonesia, 2025)
The development of technology and information presents various service products for the community. Fintech or Financial Technology is one of the online services that currently helps the community a lot. This technology is engaged in the financial industry and economy. Various types of Fintech are present to help people's financial and entrepreneurial problems. Easy and fast systems and services, making Fintech increasingly in demand. This research and scientific study aims to identify the challenges faced by these communities and propose financial technology as an alternative. Interestingly, this Fintech system continues to increase in terms of demand. Thus, it is interesting to observe in order to find out the role and successful impact of the emergence of Fintech.